2018
DOI: 10.1002/marc.201800080
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Rod‐Coil Block Copolymers on Carbon Nanotubes: A Route toward Diverse Surface Nanostructures

Abstract: In this work, it is reported that poly(γ-benzyl-l-glutamate)-block-poly(ethylene glycol) (PBLG-b-PEG) rod-coil block copolymers (BCPs) can disperse carbon nanotubes (CNTs) in solution and form various surface nanostructures on the CNTs via solution self-assembly. In an organic solvent that dissolves the BCPs, the PBLG rod blocks adsorb on CNT surfaces, and the BCPs form conformal coatings. Then, by the introduction of water, a selective solvent for PEG blocks, the BCPs in the coatings further self-assemble int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…When self‐assembly occurs in a confined space, such as spheres, cylinders (nanopores), and circles, the block copolymers are able to form diverse chiral nanostructures, including helices, helical balls, and spirals. [ 16–23 ] However, there are very limited examples to date regarding the self‐assembly of block copolymers into 2D well‐defined chiral nanoarchitectures on a confined substrate. Recent works have shown that well‐ordered nanopatterns of block copolymers can be constructed by introducing chemical or topological confinement to a substrate, [ 15,24,25 ] but these nanopatterns rarely possess chirality characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When self‐assembly occurs in a confined space, such as spheres, cylinders (nanopores), and circles, the block copolymers are able to form diverse chiral nanostructures, including helices, helical balls, and spirals. [ 16–23 ] However, there are very limited examples to date regarding the self‐assembly of block copolymers into 2D well‐defined chiral nanoarchitectures on a confined substrate. Recent works have shown that well‐ordered nanopatterns of block copolymers can be constructed by introducing chemical or topological confinement to a substrate, [ 15,24,25 ] but these nanopatterns rarely possess chirality characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…[ 28,29 ] In Step 2 , the PS microstripes on the substrate were used as templates to direct the surface self‐assembly of PBLG‐ b ‐PEG (temperature: 20 °C). [ 23,30 ] Typically, PBLG‐ b ‐PEG copolymers were dissolved in a mixed solvent of tetrahydrofuran (THF) and N,N ′‐dimethylformamide (DMF) (THF/DMF, 7/3 v/v), and the substrate was immersed in the polymer solution with the PS microstripes facing up. Then, water, a selective solvent for PEG blocks was added.…”
Section: Methodsmentioning
confidence: 99%
“…[63] Replacing the rod-like templates by PBLG loops or carbon nanotubes, the PEG-b-PBLG/PEG-b-PBDG BCPs* still enabled a helix* topology (Figure 6C). [100,104,105] Also, the same group demonstrated the co-assembly of PEG-b-PBLG/PEG-b-PBDG BCPs* with PS homopolymers into spherical assemblies with striped topologies. [106,107] It was found that chiral spiral patterns were obtainable from PEG-b-PBLG/PS and PEG-b-PBDG/PS, whereas an achiral meridian-like pattern was obtained from PEG-b-PBLG/PEG-b-PBDG/PS.…”
Section: Self-assembly Of Bcps* In Selective Solventsmentioning
confidence: 96%
“…For example, the solvent-vapor annealing method often requires complex equipment, and the procedures are time consuming. The self-assembly of block copolymers generates diverse nanostructures, [12][13][14][15] which may be a facile way to produce surface nanostructures on substrates without expensive devices or complex processes. [16,17] However, in the limited examples regarding the self-assembly of block copolymers at a selective into the solution of PBLG-b-PEG in tetrahydrofuran/N,N′dimethylformamide mixture (THF/DMF, 3/7 v/v) with the PS facing up.…”
Section: Introductionmentioning
confidence: 99%